THE ROLE OF MSMES IN LOCAL ECONOMIC IMPROVEMENT AND LABOR ABSORPTION IN INDONESIA - Kurniadi, Agus; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (Nusantara Economics and Entrepreneurships Journals, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economic landscape, contributing significantly to local economic development and employment generation. This study reviews existing literature to examine how MSMEs enhance local economies and facilitate labor absorption, particularly in rural and suburban areas. Through an extensive analysis of prior research, the study identifies key factors that influence the growth and sustainability of MSMEs, including access to capital, digitalization, policy support, and entrepreneurial education. The findings reveal that MSMEs account for over 97% of total business units in Indonesia and contribute approximately 60% to the national Gross Domestic Product (GDP) (Kementerian Koperasi dan UKM, 2023). Furthermore, MSMEs employ around 97% of the Indonesian workforce, providing significant employment opportunities, especially for lower-skilled workers and women (Tambunan, 2019). However, MSMEs face challenges such as limited access to financing, lack of technological adaptation, and insufficient market reach (OECD, 2021). The review underscores the importance of strengthening policy frameworks, enhancing financial inclusivity, and supporting digital transformation to boost MSMEs' productivity and resilience. As MSMEs continue to evolve, they hold potential for increasing Indonesia’s economic self-reliance and improving socio-economic welfare in local communities. Further research is recommended to explore the impact of specific government programs and financial interventions on MSME growth and labor dynamics